From downtown to the outskirts: a radio survey of the Orion Nebula Cluster. Issue 3 (1st July 2021) - Vargas-González, J; Forbrich, J; Dzib, S A; Bally, J
ABSTRACT: We present a newly enlarged census of the compact radio population towards the Orion Nebula Cluster (ONC) using high-sensitivity continuum maps (3–10 $μ$ Jy beam −1 ) from a total of ∼30-h centimetre-wavelength observations over an area of ∼20 × 20 arcmin 2 obtained in the C- band (4–8 GHz) with the Karl G. Jansky Very Large Array (VLA) in its high-resolution A-configuration. We thus complement our previous deep survey of the innermost areas of the ONC, now covering the field of view of the Chandra Orion Ultra-deep Project (COUP). Our catalogue contains 521 compact radio sources of which 198 are new detections. Overall, we find that 17 per cent of the (mostly stellar) COUP sources have radio counterparts, while 53 per cent of the radio sources have COUP counterparts. Most notably, the radio detection fraction of X-ray sources is higher in the inner cluster and almost constant for r > 3 arcmin (0.36 pc) from θ 1 Ori C, suggesting a correlation between the radio emission mechanism of these sources and their distance from the most massive stars at the centre of the cluster, e.g. due to increased photoionisation of circumstellar discs. The combination with our previous observations 4 yr prior lead to the discovery of fast proper motions of up to ∼373 km s −1 from faint radio sources associated with ejecta of the OMC1 explosion. Finally, we search for strong radio variability. We found changes in flux density by a factor of ≲5 within our observations and a few sources with changes by a factor >10 on long time-scales of a few years.